HUBUNGAN PENGETAHUAN DAN PERSONAL HIGIENE IBU DENGAN KEJADIAN DIARE PADA BALITA DI DESA PUDUN JULU KECAMATAN PADANGSIDIMPUAN BATUNADUA TAHUN 2018 - Siregar, Yenni Farida; Rangkuti, Nur Aliyah (Universitas Aufa Royhan, 2018)
Diarrhea is one of the most common diseases affecting children throughout the world. Diarrheal disease is still a public health problem in developing countries like Indonesia, because of its high morbidity and mortality. To find out the Relationship between Mother's Knowledge and Personal Hygiene with the Incidence of Diarrhea in Toddlers in Pudun Julu Village, Padangsidimpuan Batunadua District in 2018. The type of research used in this research is descriptive analytic using cross sectional design. Population and Samples of all mothers who have toddlers are 48 mothers, with a total sampling. Bivariate analysis is carried out to find out between the independent variable and the dependent variable. To find out that the test carried out is the square test (chi-square) and the calculation of odd ratio (OR) so that it can be known there is no statistically significant relationship with a significance level of 0.005 or a = 5%. Statistical test results obtained p value (0.019) <α (0.05) so that Ha is accepted. This means it can be seen that there is a relationship between respondent's personal hygiene with the occurrence of diarrhea in toddlers in Pudun Julu Village in 2019. It is expected that mothers of toddlers to further improve and maintain personal hygiene, around the house and the environment because of environmental hygiene, one of which is to prevent infectious diseases, especially diarrhea.